Development of a true transition state force field (TTSFF) from quantum mechanical calculations. - Madarász, A; Berta, D; Paton, R (American Chemical Society, 2016)
Transition state force fields (TSFF) treated the TS structure as an artificial minimum on the potential energy surface in the past decades. The necessary parameters were developed either manually or by the Quantum-to-molecular mechanics method (Q2MM). In contrast with these approaches, here we propose to model the TS structures as genuine saddle points at the molecular mechanics level. Different methods were tested on small model systems of general chemical reactions such as protonation, nucleophilic attack, and substitution, and the new procedure led to more accurate models than the Q2MM-type parametrization. To demonstrate the practicality of our approach, transferrable parameters have been developed for Mo-catalyzed olefin metathesis using quantum mechanical properties as reference data. Based on the proposed strategy, any force field can be extended with true transition state force field (TTSFF) parameters, and they can be readily applied in several molecular mechanics programs as well.